1980
DOI: 10.1007/bf00384569
|View full text |Cite
|
Sign up to set email alerts
|

A clonal analysis of anthocyanin accumulation by cell cultures of wild carrot

Abstract: The accumulation of anthocyanin by clones and subclones from a cell suspension culture of wild carrot (Daucus carota L.) has been measured under standard conditions. Clones which accumulate low amounts of anthocyanin were shown, by recloning after maintenance by serial passage, to have become heterogenous and to contain cells with increased accumulation of anthocyanin. There appears to be a maximum amount of anthocyanin that clones can accumulate. Clones which accumulate the maximum amount of anthocyanin were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
36
0
1

Year Published

1981
1981
2010
2010

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(39 citation statements)
references
References 14 publications
2
36
0
1
Order By: Relevance
“…The morphological heterogeneity of plant cell cultures is well known [10,13], and there are also several reports indicating a correlation between biochemical heterogeneity and the size of cell clusters. Mixtures of pigmented and non-pigmented cell groups have been reported [1,22], while enzyme activities [4,18], rates of protein synthesis, and the level of free amino acids [18] have also been found to vary with the degree of cell separation.…”
Section: Introductionmentioning
confidence: 98%
“…The morphological heterogeneity of plant cell cultures is well known [10,13], and there are also several reports indicating a correlation between biochemical heterogeneity and the size of cell clusters. Mixtures of pigmented and non-pigmented cell groups have been reported [1,22], while enzyme activities [4,18], rates of protein synthesis, and the level of free amino acids [18] have also been found to vary with the degree of cell separation.…”
Section: Introductionmentioning
confidence: 98%
“…Later, Sievert and Hildebrandt (20) noted clonal variation for the ability to grow on various carbon sources with tobacco cultures. Others have isolated clones which vary in their ability to produce anthocyanin (7), grow in the presence of ABA (22,23), utilize urea as the only source of nitrogen (21), produce nicotine (18) and grow in the absence of growth regulators (14). Collectively, these studies essentially have shown that within a population of cultured cells there exist individuals with variant forms of a particular characteristic and are each able to pass on their own forms of the characteristic to their descendents.…”
Section: Discussionmentioning
confidence: 99%
“…Aside from the numerous observations and reports concerning the general subject of phenotypic variability associated with 'tissue cul- ture,' a number of investigators have demonstrated that clonal cell lines isolated from cultured plant (1,7,11,14,15,18,(21)(22)(23) and animal (19) cell populations exhibit considerable phenotypic variability. As early as 1958, Hildebrandt observed differences among cells for color, growth rate, texture, morphology, nutritional requirements, and susceptibility to virus (10).…”
Section: Discussionmentioning
confidence: 99%
“…As an example, Ogino et al (1978) showed the necessity of several successive subclonings to select tobacco cell clones producing large amounts of nicotine. As another example, Dougall et al (1980), usingDaucus carota cells producing anthocyanin, observed a cell heterogeneity in a suspension culture even if it is issued from a single cell by a cloning procedure. They concluded that these variations did not seem to be due to a stable modification of genetic information.…”
mentioning
confidence: 97%